Conflict and Decision-Making in Soviet Russia : A Case Study of Agricultural Policy, 1953-1963 - Ploss, Sidney I. (Book collections on Project MUSE., 1965)
This discussion of agricultural policy in the decade after Stalin shows how decisions are made and then enforced. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.